(untitled) (GIST – Education and Learning Research Journal, 2021)
Gist agradece a los siguientes revisores por su contribución: Edgar Lucero Babativa, Universidad de La Salle, Colombia Fredy Rozo, Fundación Universidad de América, Colombia Jair Ayala-Zárate, Educational Testing Services, Colombia Ayşegül Takkaç-Tulgar, Atatürk University, Turkey Diana Rocío Umaña Buitrago, Universidad del Rosario, Colombia Paul Abraham, Simmons College, USA Juan Carlos Torres Rincón, Universidad de La Sabana, Colombia Juan Ríos Vega, Bradley University, USA Claudia Acero, Universidad de La Sabana, Colombia Rigoberto Castillo, Universidad Distrital Francisco José de Caldas, Colombia Adriana Castañeda Londoño, Universidad de los Andes, Colombia Sanja Škific, University of Zadar, Croatia Alexander Ramírez, Universidad del Valle, Colombia Meral Gözüküçük, Kafkas University, Turkey Margarita López, Universidad de Caldas, Colombia Diego Ubaque, Universidad Distrital Francisco José de Caldas, Colombia